Gamma knife radiosurgery for cerebral cavernous malformations: biologically effective dose predicts therapeutic outcomes - Shi, Xiaoman; Deng, Hao; Wu, Yang; Gao, Yuan; Huang, Xinyuejia; Yin, Senlin; Wang, Wei (Frontiers in Neurology, 2025)
BackgroundGamma knife radiosurgery (GKRS) is an established option for cerebral cavernous malformations (CCMs) when microsurgical resection is not feasible. Lesion location strongly influences treatment strategy. The biologically effective dose (BED), introduced by J. F. Fowler, has been widely discussed in radiobiology but not evaluated in CCMs.MethodsA retrospective cohort study was conducted on 107 patients with 123 CCMs treated by GKRS at West China Hospital between June 2020 and December 2022. Post-GKRS hemorrhage was defined as symptomatic bleeding. The annual hemorrhage rate (AHR) quantified bleeding risk, and effective volumetric control was defined as ≥ 20% volume reduction. Clinical outcomes were categorized as improved, stable or worsened.ResultsThe mean age was 41 years, and 59.8% were female. Pre-GKRS hemorrhage was most frequent in brainstem (78.6%) and basal ganglia/thalamic lesions (73.3%). During follow-up, 13 patients (10.6%) experienced hemorrhage and AHR decreased from 13.6 to 4.3% per 100 lesion-years (IRR = 0.314; p < 0.001). BED was an independent protective factor against postoperative hemorrhage (HR = 0.964, p = 0.044) and significantly associated with volumetric and clinical control.ConclusionGKRS significantly reduced hemorrhage risk and promoted lesion regression in CCMs. BED was identified as a strong independent predictor of hemorrhage control, volume response and clinical outcomes, outperforming conventional dose metrics. These findings suggest that BED may guide personalized radiosurgical dose optimization for CCMs.